Environmental Awareness Among the Students of the Faculty of Education - Buthaina Shaheed (Journal of Global Pharma Technology, 2018)
Student search slice represents the extract of the most important components of society which can play a big role in addressing the various problems and obstacles in order to follow the technological development that the purpose of this study: identify the environmental awareness among the students of the Faculty of education. Detect indications of differences to environmental awareness among students depending on the variable gender (male, female) 3. detect indications of differences to environmental awareness due to the variable competence (knowledge, human) research has been determined by the College of education for the academic year 2017 research goals requests creation of a tool to measure the level of awareness Ecosystem then ascertain its truthfulness and consistency through displayed on a group of experts in psychology and ecology researchers applied the scale on a sample of (400) then the data were analyzed using statistical case for Social Sciences (SPSS) results: environmental awareness among students Average education. No statistical differences in the level of environmental consciousness according to heterosexual (male, female). There are differences in the level of environmental awareness due to the variable competence (knowledge, human). Based on these results, we offer a number of al astenta. 1. to adopt environmental sciences department at Faculty of science scientific strategies to promote environmental awareness through many seminars and set up seminars and awareness and educational lectures for all cadres in the University as well as the various strata of society. 2. Activate the role of the media, working on achieving compliance with laws and regulations and avoid all illegal means to be environmentally friendly. From: numerous studies and researches on this subject have great importance on individual and community health.